Meningkatkan Kemampuan Literasi Numerasi Matematika Siswa SMA melalui Model Problem Based Learning - Aldira Eka Fauzanah; Nizaruddin Nizaruddin; Linda Koes Puji Astuti; Rasiman Rasiman (Departement of Mathematics Education, 2024)
This research is motivated by low numeracy literacy skills which are a crucial problem in educational development, especially at SMA Negeri 2 Semarang. This research aims to find out whether the Problem Based Learning (PBL) model is effective in improving high school students' mathematical numeracy literacy skills. This research uses the classroom action research (PTK) method by applying the Kurt Lewin model which includes planning, implementation, observation and reflection stages. The subjects of this research were 36 class X.8 students. Data was collected through a numeracy literacy skills test at the pre-cycle, cycle I and cycle II stages. The results of the research show that the actions taken succeeded in achieving success indicators with more than 75% of students achieving completeness, namely 79.4% or 80%. The implications of this research show that the PBL model can have a positive impact on student learning outcomes in improving mathematical numeracy literacy skills in high school.